2014
DOI: 10.1371/journal.pone.0113788
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Mediated Antioxidative Mechanism in Yeast through the Activation of the Transcription Factor Mac1

Abstract: The budding yeast Saccharomyces cerevisiae possesses various defense mechanisms against environmental stresses that generate reactive oxygen species, leading to growth inhibition or cell death. Our recent study showed a novel antioxidative mechanism mediated by nitric oxide (NO) in yeast cells, but the mechanism underlying the oxidative stress tolerance remained unclear. We report here one of the downstream pathways of NO involved in stress-tolerance mechanism in yeast. Our microarray and real-time quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 47 publications
3
17
1
Order By: Relevance
“…From the results of the nitrosative stress tolerance analyses, Δrib1 cells showed higher sensitivity to the acidified NaNO 2 condition than WT cells, indicating that the physiological expression level of RIB1 contributes to nitrosative stress tolerance. This is in contrast with our previous microarray analysis 17 , which indicated that RIB1 www.nature.com/scientificreports www.nature.com/scientificreports/ is not induced by NO treatment. On the other hand, fHb, one of the major NO detoxifying enzymes, is upregulated after exposure to NO through the activation of the transcription factor Fzf1 in S. cerevisiae or Cta4 in Candida albicans [31][32][33] .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…From the results of the nitrosative stress tolerance analyses, Δrib1 cells showed higher sensitivity to the acidified NaNO 2 condition than WT cells, indicating that the physiological expression level of RIB1 contributes to nitrosative stress tolerance. This is in contrast with our previous microarray analysis 17 , which indicated that RIB1 www.nature.com/scientificreports www.nature.com/scientificreports/ is not induced by NO treatment. On the other hand, fHb, one of the major NO detoxifying enzymes, is upregulated after exposure to NO through the activation of the transcription factor Fzf1 in S. cerevisiae or Cta4 in Candida albicans [31][32][33] .…”
Section: Discussioncontrasting
confidence: 99%
“…A low level of NO also plays a role in oxidative stress tolerance in bacteria 15 . In the budding yeast Saccharomyces cerevisiae, we found that NO confers high temperature stress tolerance through the activation of the copper-related transcription factor Mac1 [16][17][18] . On the other hand, an excessive level of RNS including NO could cause nitrosative stress leading to cellular damage or death.…”
mentioning
confidence: 99%
“…Interestingly, in our study, L-NAME increased the accumulation of superoxide radicals during AmB treatment, while decreasing the proliferative capacity of cells in the presence of AmB, and thus decreasing survival. It seems that a nitric oxide radical-dependent tolerance system is switched on upon AmB treatment in yeast, perhaps similar to the system recently described by Nasuno and colleagues [ 56 ]. In that study, a downstream pathway of nitric oxide radicals involved in high-temperature stress tolerance in yeast was unravelled.…”
Section: Discussionsupporting
confidence: 67%
“…In that study, a downstream pathway of nitric oxide radicals involved in high-temperature stress tolerance in yeast was unravelled. They showed that nitric oxide radicals activated the transcription factor Mac1 that on its turn induced the CTR1 gene and resulted in increased cellular copper levels, which then resulted in activation of Sod1, a superoxide dismutase [ 56 ]. Alternatively, it could also be that nitric oxide activates, potentially via S-nitrosylation, AmB tolerance pathways such as the yeast HOG pathway [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CTR1 , CTR3, and FRE1 genes/proteins in the category of copper iron transport were significantly upregulated. These three genes are all regulated by transcription factor Mac1p [33], but the expression of MAC1 was not significantly regulated in either the transcriptome or the proteome. In addition to CTR1 , CTR3 , and FRE1 , other genes downstream of MAC1—FRE7 , IRC7, and REE1 showed various degrees of upregulation in the transcriptome and proteome (Fig.…”
Section: Resultsmentioning
confidence: 99%